Reliable characterization of organic dielectrics degraded by high electric field - Djamila Abid; Hocine Hadi; Mohammed Benzohra; Boulos Youssef (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
The study of the degradation of organic dielectrics is of great interest for industrial applications, especially in electrical industry. So great, that other applications are also being developed in the fields of optical communications, information storage, stacked memories or manufacturing new components in micro technology, mainly in the fields of MEMS and sensors. Under the same conditions of temperature and of high intensity electric field during operation, we present results on Poly Ethylene Terephthalate (PET) which is the most useful material; the degradation considered here is induced by high electric field in ambient atmosphere with a high voltage range scaled around on 12kV during 1h.The physical and thermal characterization is carried out by an implementation of an experimental technique very fine high sensitivity and high accuracy measures such as Broadband Dielectric Spectroscopy (BDS) and Differential Scanning Calorimetry (DSC). Phase transition, relaxation mode changes, molecular relaxation and trapping effect will be discussed.